Prognostic Modeling of Deleterious IDUA Mutations L238Q and P385R in Hurler Syndrome Through Molecular Dynamics Simulations - Madhana Priya Nanda Kumar; Esakki Dharsini Selvamani; Archana Pai Panemangalore; Sidharth Kumar Nanda Kumar; Vasundra Vasudevan; Magesh Ramasamy (Pharmaceuticals, 2025)
MPS I (Mucopolysaccharidosis type I) is a rare lysosomal storage disease originating from the deficiency of the enzyme alpha-L-iduronidase, encoded by the IDUA gene, which impairs the degradation of glycosaminoglycans (GAGs) and diminishes biological functioning across several organs. Background: Out of the eleven MPS disorders, MPS I includes three syndromes, of which the first, named Hurler syndrome, affects the most. Methods: Several in silico tools were used, such as ConSurf (73 variants), Mutation Assessor (69 variants), PredictSNP, MAPP, PhDSNP, Polyphen-1, Polyphen-2, SIFT, SNAP, PANTHER, MetaSNP (24 variants); Missense 3D-DB (11 variants) and AlignGVGD (eight variants) for physicochemical properties; and I-Mutant, Mupro, CUPSAT, and INPS for stability predictions (four variants). Results: A molecular docking study was performed for the two variants: L238Q and P385R scored −7.22 and −7.05 kcal/mol, respectively, and the native scored −7.14 kcal/mol with IDR as the ligand. Molecular dynamics anticipated how these molecules fluctuate over a period of 100 nanoseconds. Conclusions: Alpha-L-iduronidase enzyme has a critical role in the lysosomal degradation of glycosaminoglycans. According to the comparative analysis of the three structures by MDS, P385R had the least stability in all aspects of the plots. Our study demonstrates that the mutation significantly alters protein stability and binding efficiency with the ligands.